A ROAD MAP FOR THE TRANSITION TO A CARBON-FREE ECONOMY BASED ON THE ENERGY INNOVATIONS TRANSFER - Vakulenko, Ihor; Matvieieva , Yuliia; Opanasiuk , Yuliia; Taraniuk , Karina; Rosokhata , Anna (Socio-economic relations in the digital society, 2024)
This study aims to analyze existing scientific approaches to developing roadmaps in energy and innovation, identify key challenges hindering the transition to a carbon-neutral economy, and develop practical recommendations for Ukraine. Particular emphasis is placed on identifying and integrating legislative, economic, technological, and social aspects into energy innovation transfer to ensure an effective and sustainable transition. A literature review was conducted using key terms such as "roadmap," "energy," and "innovation," which allowed for the identification of the most relevant trends and approaches in this field. The article outlines the main challenges Ukraine faces in transitioning to a carbon-neutral economic model based on the transfer of energy innovations. These challenges include legislative barriers, insufficient economic incentives, technological difficulties, and social factors that slow down the implementation of innovations. Based on the identified problems and existing trends, a roadmap for Ukraine’s transition to a carbon-neutral economy was developed, covering four key areas: legislative, economic, technological, and social. The sequence of steps and actions necessary to implement the transition scenario is detailed and presented visually. The article offers specific practical recommendations for Ukraine regarding the implementation of the roadmap, including necessary legislative changes, economic incentives, investments in technology, and measures to increase social awareness and support. Thus, this article makes an essential contribution to the scientific and practical discourse on the transition to a carbon-neutral economy, particularly in the context of Ukraine, and can serve as a foundation for further research and policy development in this area.